A Letter to Harvey Milk : Short Stories - Newman, Leslea (Book collections on Project MUSE., 2004)
"This collection of stories offers a perspective on current issues of homosexuality and anti-Semitism and lends a voice to those experiencing growing pains and self-discovery. Newman's readers accompany her quirky Jewish characters through all kinds of experiences, from an initial lesbian sexual encounter to being sequestered in a college apartment after paranoid Holocaust flashbacks. In these stories, characters anxiously discover their lesbian identities while beginning to understand, and finally to embrace, their Jewish heritage."--Jacket